1994
DOI: 10.1061/(asce)0733-9445(1994)120:8(2377)
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Size Effect: Review of Evidence for Concrete Structures

Abstract: The paper reviews experimental evidence on the size effect caused by energy release due to fracture growth during brittle failures of concrete structures. The experimental evidence has by now become quite extensive. The size effect is verified for diagonal shear failure and torsional failure of longitudinally reinforced beams without stirrups, punching shear failure of slabs, pull-out failures of deformed bars and of headed anchors, failure of short and slender tied columns, double-punch compression failure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 25 publications
(25 reference statements)
1
22
0
2
Order By: Relevance
“…The stress failure of temporarily compressed concrete is an important issue from both the point of view of durability and the safety of constructions made of cement composites [4][5][6]. Based on research, it was found that three stages, which are qualitatively different in terms of damage to the concrete structure, can be identified in the concrete failure process.…”
Section: Introductionmentioning
confidence: 99%
“…The stress failure of temporarily compressed concrete is an important issue from both the point of view of durability and the safety of constructions made of cement composites [4][5][6]. Based on research, it was found that three stages, which are qualitatively different in terms of damage to the concrete structure, can be identified in the concrete failure process.…”
Section: Introductionmentioning
confidence: 99%
“…While the laboratory setup can be easily reproduced, the test outcomes are strictly dependent on the choice of various parameters as the mechanical properties of the employed materials, the size of specimens and the anchorage embed depth. The influential works of Eligehausen and Sawade [12], Bažant et al [13], Ožbolt et al [14], Karihaloo [15] emphasized the structural size effect on the pullout test and its influence on the energy dissipated in the cracking process. Most recent advances are related to the possibility of testing the coupling between FRP composites and concrete [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Since the tensile strength of concrete is normally evaluated by the split-tensile (Brazilian) test, the moment tensor analysis of AE was applied to clarify the tensile failure process at the meso-scale in concrete (Reinhardt et al 2007;Mondringin et al 2011). Concerning the tensile strength of concrete, a variety of findings have been attained and recently the nucleation of the fracture process zone is highlighted in fracture mechanics (Bazant 1993;Bazant et al 1994). From AE research, it is clarified that similar nucleation processes of the fracture process zone could reasonably lead to comparable tensile strengths by the split-tensile test and by the direct tensile test .…”
Section: Introductionmentioning
confidence: 99%